Establishing Conversion Values for New Currency Unions : Method and Application to the planned Gulf Cooperation Council (GCC) Currency Union - Kamar, Bassem (IMF Working Papers; Working Paper ;, 2009)
A key issue in creating a new currency union is setting the rates to convert national currencies into the new union currency. Planned unions in the Gulf region and Africa are seeking methods to set the conversion rates when their new currencies are created. We propose a forward-looking econometric methodology to determine conversion rates by calculating the degree of misalignment in the real exchange rate, and apply it to the GCC currency union. For each GCC currency, we identify the year at which the economy is the closest to its internal and external equilibrium, and then estimate the degree of misalignment in the bilateral real exchange rate vis-a-vis the U.S. dollar based on WEO forecasts until 2013. Application of the methodology to other regions is also considered.